Costume design and illustration - Arelleno, Carlo; Arelleno, Carlo; Boutte Jr., Phillip; Chen, Kevin; Christensen, Keith; Cordella, Christian; Francisco, Anthony; Marantz, Jerad S.; Page, Neville; Robertson, Scott; Sekeris, Constantine (Design Studio Press, 2014)
Spearheaded by Constantine Sekeris, author of "MetamorFX," this book is an in-depth look at costume design and illustration. Showcasing an educational process breaking down the problematic areas of costume design for the film, video game and animation industries. From 10 top leading artists in the field, this title will includes a wide range of aesthetic and design solutions. Learn how to design and illustrate a costume from start to finish with educational tips and the process from sketches to finished Photoshop images, to 3D ZBrush sculptures, to fabrication.